Chlamydial infection: an accurate model for opportunistic screening in general practice. Issue 4 (5th August 2003) - Verhoeven, V; Avonts, D; Meheus, A; Goossens, H; Ieven, M; Chapelle, S; Lammens, C; Van Royen, P
Abstract : Objectives: To estimate the prevalence of Chlamydia trachomatis in women in general practice and to assess risk factors associated with infection. Methods: The study was carried out in 2001–2 in different general practices in Antwerp, Belgium. Sexually active women, visiting their general practitioner for routine gynaecological care (mostly pill prescription or PAP smear), were offered opportunistic screening for chlamydia. 787 participants aged 15–40 delivered a self taken vaginal sample and filled in a questionnaire which included questions on demographic variables, urogenital symptoms, sexual history, and sexual behaviour. Samples were tested for presence of chlamydial DNA by means of a ligase chain reaction (LCR) assay, and positives were confirmed by two other amplification assays (PCR and SDA). Results: Overall prevalence was 5.0% (95% CI: 3.5 to 6.5). Determinants of infection in logistic regression analysis were age 18–27 years, >1 partner in the past year, no use of contraceptives, frequent postcoital bleeding, having a symptomatic partner, painful micturition, and living in the inner city. The area under the ROC curve in the full model was 0.88. Selective screening based on a combination of the five first determinants detects 92.3% of infections in this sample; 37.5% of the population would need to be screened. Conclusion: Targeted screening for chlamydial infection is possible, even in a heterogeneous group of general practice attendants. Implementing this model would require considerable communication skills from healthcare providers.